C60 fullerene improves the recovery of biomechanical parameters of muscle soleus contraction in rats after chronic alcoholization - Д. М. Ноздренко; В. Нан; Т. Ю. Матвієнко; К. І. Богуцька; Т. Я. Шевчук; В. П. Берест; Ю. І. Прилуцький (Біофізичний вісник)
Background: Recovery of biomechanical parameters of contraction of muscles damaged by alcoholic myopathy is a rather complex and long-term process. Therefore, the search for effective therapeutic means for its acceleration is an extremely urgent task in biomedicine.